DELIMITATION OF FREEDOM OF CONTRACT PRINCIPLE AND JUDGE’S CORRECTIVE FUNCTION IN ASSESSING THE PARTIES’ POSITIONS ON AN AGREEMENT - Muhammad Natsir Asnawi; Edi Hudiata (Fakultas Hukum Universitas Gadjah Mada, 2017)
The principle of freedom of contract established for much types of contract. This principle concerned onhow parties state their mind freely into the contract clauses. The primordial concept of freedom of contractwas reduced based on Indonesian judiciary practice. This normative research of law tries to analyse theconcept alteration of meaning and implementation of freedom of contract in Indonesian Judiciary practice.The Supreme Court of Indonesia through its precedent provides broader authority to the Judges in orderto supervise and remedy the unbalance stand of parties on a contract they state which causes one or moreconsiderations cannot be or make difficulties to perform. The result of this research show us that freedomof contract principle is confined by proportionality, appropriateness, and justice principles toward partiesin a contract stated.